Modified load‐modulation network with two π‐type high‐pass equivalent λ/4 lines for wideband compact GaN MMIC Doherty power amplifier design. Issue 16 (2nd May 2021) - Liu, Rui‐Jia; Zhu, Xiao‐Wei; Xia, Jing; Jiang, Yi‐Fan; Chen, Peng; Yu, Chao; Ge, Chuan
Abstract: A modified load‐modulation network to design a fully integrated wideband Doherty power amplifier (DPA) from 4.6 to 5.5 GHz is presented in this letter. The modified load‐modulation network uses only two π‐type high‐pass equivalent quarter wavelength transmission lines (QWTLs). Unlike the existing methods, the bandwidth of the load‐modulation network composed of two merged π‐type equivalent QWTLs is broadened. Furthermore, a drain bypass capacitor compensation method is proposed to reduce the leakage of RF power after the drain supply inductors are merged. For verification, a wideband monolithic microwave integrated circuit DPA was designed and fabricated using a 0.25‐μm gallium nitride based high‐electron‐mobility transistor process. Measurement results show that a saturated power of 41.6–42.4 dBm, a saturated drain efficiency (DE) of 65.3–72%, and a 6‐dB back‐off DE of 45–55.4% are achieved from 4.6 to 5.5 GHz. Using a 160‐MHz orthogonal frequency‐division multiplexing signal with a peak‐to‐average power ratio of 6.2 dB, the high average efficiency of 49% with an adjacent channel leakage ratio of –47.2 dBc after linearisation was obtained at an average output power of 35 dBm at 4.9 GHz.